Spectroscopic Investigations, Anti-bacterial Activities and DNA-interactions of Metal Complexes (Cr(III), Zn(II), Ni(II)) Containing Phendione Ligand (Journal of Scientific Research, 2015)
The transition metal complexes [Cr(acac)2(phendione)]Cl, [Zn(acac)2(phendione)], [Ni(acac)2(phendione)], [Zn(phendione)3](ClO4)2 and [Ni(phendione)2](ClO4)2 were synthesized from 1, 10-phenanthroline-5, 6-dione (phendione). The phendione ligands and its metal complexes were characterized by FTIR, UV-Visible spectroscopy, PL study and in some cases by GC-MS. The red emission band of complex [Zn(acac)2(phendione)] was observed by excitation at 250 nm. DNA binding activities of the complexes were studied by DNA Gel Electrophoresis.  DNA binding studies of the synthesized compounds showed that the metal complexes are strong DNA binding and cleaving agents. The [Ni(phendione)2] (ClO4)2 complex was the most effective DNA binding and cleaving agent and [Cr(acac)2(phendione)]Cl complex shows relatively lower affinity to the DNA. The metal complexes easily cause DNA degradation or cleavage (after 2.5 h) with genomic DNA rather than plasmid DNA. Antimicrobial activity studies revealed that all metal complexes of phendione showed efficient resistance to bacteria. The [Cr(acac)2(phendione)]Cl complex showed most potential antimicrobial activities against the bacteria Escherichia coli with an annular radius of the inhibitory zone, 4.33.